2018
DOI: 10.1007/s13224-018-1092-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion Practices in Obstetrics: Our Experience

Abstract: 1.3% of all obstetric patients from our center had blood components transfusion during the study period. Postpartum hemorrhage, placental causes and anemia are the commonest causes for need of transfusion in obstetric practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 18 publications
6
14
0
5
Order By: Relevance
“…13 In another study by Chawla et al, it was observed that 66% patients were transfused with fresh frozen plasma, 79% patients were transfused with packed cell volume transfusion, 15% patents were transfused with platelet transfusion. 4 The Ten Commandments for the transfusion practice in medicine state that transfusion should only be used when the benefits outweigh the risks and there are no appropriate alternatives, and laboratory tests should not be the sole deciding factor for transfusion. 14 The guidelines for blood transfusion to obstetrics (Ob)/gynecology (Gy) patients are available.…”
Section: Resultsmentioning
confidence: 99%
“…13 In another study by Chawla et al, it was observed that 66% patients were transfused with fresh frozen plasma, 79% patients were transfused with packed cell volume transfusion, 15% patents were transfused with platelet transfusion. 4 The Ten Commandments for the transfusion practice in medicine state that transfusion should only be used when the benefits outweigh the risks and there are no appropriate alternatives, and laboratory tests should not be the sole deciding factor for transfusion. 14 The guidelines for blood transfusion to obstetrics (Ob)/gynecology (Gy) patients are available.…”
Section: Resultsmentioning
confidence: 99%
“…Gebelik ve doğum eylemi süresince kan ürünü transfüzyonun gereksinimine yol açan birçok çalışmada ortak risk faktörleri bulunmuştur (4,9). Bu faktörler plasental patolojiler (plesanta previa, insersiyon anomalisi, dekolman, rest plasenta), anemi, aşırı uterus distansiyonu (çoğul gebelik, polihidramnios), preeklampsi/eklampsi, preterm eylem, doğum eyleminin indüksiyonu, travma, acil sezaryen ve operatif doğumu içerir (3,4,9).…”
Section: Discussionunclassified
“…Uterin atoni, postpartum kanamaların %70-80'inden sorumlu olup en sık nedendir (1,7). Gebelikte kan transfüzyonunlarının %24-35 inde neden uterin atoni olarak saptanmıştır (3,4). Bizim çalışmamızda bu oran %18,9 olarak bulunmuştur.…”
Section: Discussionunclassified
See 2 more Smart Citations